A measurement-based path loss model for wireless links in mobile ad-hoc networks (MANET) operating in the VHF and UHF band - Fischer, Jörg Dieter; Heuberger, Albert; et al. (Proceedings IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2012)
For the development of future mobile-to-mobile communication systems, realistic channel models are required. Available models are aiming at broadcasting applications using high antenna towers and are therefore not applicable for mobile-to-mobile applications like mobile ad-hoc networks (MANET). In this paper, measurements of the path loss using car-mounted receiver and transmitter antennas are presented. Based on the measurement results, a new path loss model is proposed. It is shown that this model provides a more realistic prediction of the path loss for MANET systems in the VHF and UHF band than the widely used Okumura-Hata model. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.ameasu